To find the numerical equivalent of \( 12^{-5} \cdot 12^{7} \), we can apply the product rule of integer exponents. The product rule states that when multiplying two expressions with the same base, we add their exponents. This can be mathematically expressed as:
\[ a^m \cdot a^n = a^{m+n} \]
In our case, the base \( a \) is \( 12 \), and the exponents are \( -5 \) and \( 7 \). According to the product rule, we can combine the exponents as follows:
\[ 12^{-5} \cdot 12^{7} = 12^{-5 + 7} \]
Now, we simplify the exponent:
\[ -5 + 7 = 2 \]
Thus, we have:
\[ 12^{-5} \cdot 12^{7} = 12^{2} \]
Next, we calculate \( 12^{2} \):
\[ 12^{2} = 12 \cdot 12 = 144 \]
So, the numerical equivalent of \( 12^{-5} \cdot 12^{7} \) is
\[ \boxed{144} \]